Deregulation in Job Creation Law: The Future of Indonesian Labor Law - Nabiyla Risfa Izzati (Faculty of Law, Universitas Padjadjaran, 2022)
A new era in Indonesian labor policy has begun with the recent passage of Law Number 11 of 2020 on Job Creation. The Law modifies dozens of legislations to make business performance easier and strengthen the national investment climate. In doing so, the Law deregulated some key Indonesian labor law policies, reducing previous labor rights formerly governed by Law Number 13 of 2003 on Manpower. The Job Creation Law also seems to increase labor market flexibility. It makes businesses simpler by the provision to hire workers through an outsourcing system or legalizing longer fixed-term contracts, which will make the labor market more precarious for workers in the long run. The study aims to analyze whether deregulation is a way forward for Indonesian labor law and what impact it might bring on workers. The study found solid evidence that the Indonesian government is currently underway on its mission to deregulate labor regulations. This may impact badly on workers, as many labor protections previously mandated by law are reduced. Therefore, workers must strengthen their bargaining position through collective bargaining and reinforcing the trade union to survive in the post-Job Creation Law era.DOI: https://doi.org/10.22304/pjih.v9n2.a3